2019
DOI: 10.3390/ijms20235878
|View full text |Cite
|
Sign up to set email alerts
|

Pemafibrate Prevents Retinal Pathological Neovascularization by Increasing FGF21 Level in a Murine Oxygen-Induced Retinopathy Model

Abstract: Large-scale clinical trials, such as the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) and the Action to Control Cardiovascular Risk in Diabetes (ACCORD) studies, have shown that the administration of fenofibrate, a peroxisome proliferator-activated receptor alpha (PPARα) agonist, suppresses the progression of diabetic retinopathy. In this paper, we reveal a therapeutic effect of a selective PPARα modulator (SPPARMα), pemafibrate, against pathological angiogenesis in murine models of retinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 36 publications
8
55
0
Order By: Relevance
“…Several studies have shown that pemafibrate has therapeutic effects on retinal diseases [ 114 , 115 , 116 ]. Our group showed that oral administration of pemafibrate, but not fenofibrate, increased plasma fibroblast growth factor 21 (FGF21) levels in OIR and inhibited retinal neovascularization through the inhibition of HIF-1α and Vegfa expressions [ 115 ]. In addition, long-acting FGF21 inhibited HIF activity in a photoreceptor cell line under hypoxic conditions [ 115 ].…”
Section: Functions Of Spparmα In the Eyementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that pemafibrate has therapeutic effects on retinal diseases [ 114 , 115 , 116 ]. Our group showed that oral administration of pemafibrate, but not fenofibrate, increased plasma fibroblast growth factor 21 (FGF21) levels in OIR and inhibited retinal neovascularization through the inhibition of HIF-1α and Vegfa expressions [ 115 ]. In addition, long-acting FGF21 inhibited HIF activity in a photoreceptor cell line under hypoxic conditions [ 115 ].…”
Section: Functions Of Spparmα In the Eyementioning
confidence: 99%
“…Our group showed that oral administration of pemafibrate, but not fenofibrate, increased plasma fibroblast growth factor 21 (FGF21) levels in OIR and inhibited retinal neovascularization through the inhibition of HIF-1α and Vegfa expressions [ 115 ]. In addition, long-acting FGF21 inhibited HIF activity in a photoreceptor cell line under hypoxic conditions [ 115 ]. Furthermore, we reported that oral administration of pemafibrate increased serum FGF21 levels in the streptozotocin-induced diabetic mouse model and preserved retinal function through maintaining the expression of synaptophysin which regulates synaptic vesicle endocytosis [ 114 ].…”
Section: Functions Of Spparmα In the Eyementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several groups have shown that administration of a PPARα agonist increases fibroblast growth factor 21 (FGF21) [11,12]. A recent study shows that a selective PPARα modulator (SPPARMα) prevents pathological neovascularization in a mouse model by increasing circulating FGF21 [12]. FGF21 is a secreted protein that is comprised of 209 amino acids [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hypoxia and ROS, HIF-1α expression can be induced by numerous other factors, including nitric oxide (NO), in ammatory cytokines such as TNF-α, pro-in ammatory factors such as hormone-like growth factors such as TGF-β (5). As reported by some researches (6,7), HIF-1α expression may also be reduced by FGF21, a multifunctional factor with the protective effects on diabetic complications and energy hemostasis (8). VEGF is also up-regulated upon stimulation of such factors.…”
Section: Introductionmentioning
confidence: 99%